An Empirical Analysis of Africa Continental Free Trade Area Economic Growth Prospects in the SADC Region: Evidence Using Autoregressive Distributed Lag-PMG Estimation Techniques - Chiranga, Ngonidzashe; Mosikari, Teboho J.; Zerihun, Mulatu F. (International Journal of Economics and Financial Issues, 2024)
Inter-SADC trade relations of indebted small countries and their potential of ushering economic growth from AfCFTA are unclear in both the short and long run. The study aims to empirically examine if there are AfCFTA economic growth prospects for SADC nations in the short and long term through an examination of the trade openness-economic growth nexus, and how the external debt impacts economic growth. A panel of eight SADC countries is used from a period spanning 1996-2022. The study employs Autoregressive Distributed Lag (ARDL) and the Pooled Mean Group (PMG) estimation techniques. The findings suggest that trade openness impacts economic growth positively at the 1% level in the long run, whereas external debt impacts economic growth negatively at the 1% level in both the long and short run. The study also finds that causality runs from economic growth to trade openness and is unidirectional. SADC nations are urged to minimise the overreliance on external debt in the funding of domestic consumption needs as it has negative consequences on economic growth in the long term.